Patients’ preferences and the efficacy of a hybrid model of a minimal contact nasal mask in patients with sleep apnea treated with CPAP - Magali Blanco; Veronica Jaritos; Glenda Ernst; Alejandro Salvado; Facundo Nogueira; Eduardo Borsini (Sleep Science, 2018)
Objectives: To evaluate patient`s satisfaction, efficacy and adherence to CPAP with a hybrid nasal mask (DW) we tested patients with OSA in unattended setting under real-life conditions. Material and Methods: Prospective, comparative study using DW mask 7 days against habitual mask in patients adapted to CPAP therapy. Results: We analyzed 52 patients: 35 men (67%) with IAH mean; 24.3±12.3 events/hour. At baseline mean compliance of 5.42±1.83 hours/night. After using DW mask, patients reported fewer marks, more comfort, greater partners acceptance, easier to use and was ranked higher to preventing leaks; p<0.05, and adherence (1 more hour per night, p>0.0042). Differences were not found in pressure 90th-95th percentile (9.6±9.2 cm of H2O, p<0.5), leaks (19.8±17 liters/min. p<0.37) or residual AHI (3.38±3.05 events/hour. p<0.93). Conclusion: In an uncontrolled non-randomized study, patients can use DW mask with similar leak level and better adherence as compared to conventional masks.